ОБУЧЕНИЕ ИДИОМАТИЧЕСКИМ ВЫРАЖЕНИЯМ АНГЛИЙСКОГО И УЗБЕКСКОГО ЯЗЫКОВ ЧЕРЕЗ СРАВНИТЕЛЬНЫЙ АНАЛИЗ - Калабаева, М.А. (SCIENCE and SOCIETY, 2024)
In this article, the author compares and analyzes Uzbek and English idioms, the differences between which are due to the difference in cultural and historical experience and lifestyle of the two peoples, as well as the natural and climatic conditions of their residence.